(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2022)
Health organizations face several challenges including economic crisis, new patients’ demands and fake news. These companies resort to corporate communication initiatives to protect their brands and this way reinforce their strategic positionings. Since the COVID 19 outbreak started in 2020, many of these organizations have been accused of lying concerning masks, vaccines or side effects. This literature review paper aims to analyse how quality information is a priority for health organizations interested in building a reputed brand. To do that, we carried out a literature review about health communication (interpersonal, internal, and external initiatives), health education, post-truth and fake news; we analysed some fake news spread since December 2019 concerning the COVID 19 outbreak, as well as their impact on health organizations’ reputation; and, finally, we proposed a Decalogue for these organizations on how to implement corporate communication strategies for facing fake news. We concluded that these organizations should prioritize a corporate communication approach, promote research on communication and establish multidisciplinary teams integrated by expert in communication and public health.